System for the heterologous expression of NS1 protein of H9N2 avian influenza virus in the ciliate Tetrahymena thermophila - HUANG, Yu; GONG, Hui; CHEN, Cuiteng; CHI, Hongshu; ZHU, Chunhua; FU, Guanghua; LIU, Xiaodong; CHEN, Zhen (Journal of Veterinary Medical Science, 2018)
Tetrahymena is commonly used as an alternative eukaryotic system for efficiently expressing heterologous genes. In this study, we inserted the non-structural (NS) 1 gene of avian influenza virus (AIV) into the shuttle vector pD5H8 and transformed conjugating T. thermophila with the recombinant plasmid pD5H8-NS1 by particle bombardment. Positive transformants were selected with paromomycin. We demonstrated that the NS1 protein could be expressed steadily following induction with cadmium in this Tetrahymena system. An enzyme-linked immunosorbent assay detection method was preliminary established using the expressed protein as coating antigens for serodiagnosis. This is the first study in which a Tetrahymena expression system was employed for the expression of the AIV NS1 protein, and it provides a good basis for the development of differential diagnostic kits and vaccines for the prevention and control of avian influenza.